Estudo do comportamento químico de heterociclos trifluormetil substituídos em reações com DAST - Porte, Liliane Medianeira Favero (2011)
This work describes the study of the chemical behavior of trifluoromethyl substituted heterocycles as 1H-pyrazoles, 2-pyrazolines, 2H-cromenones and isoxazolines in reactions with DAST, with the aim of evaluating possible reactions in the oxygenated sites, aiming mainly the insertion of fluorine atoms in these molecules. Trifluoromethylated heterocycle precursors such as 1H-pyrazoles (2), 2-pyrazolines (6, 8), 2H-cromenones (10-14), isoxazolines (20) were obtained from cyclic and acyclic trifluoroacetylated vinyl ethers (1) and hydrazines, hydrazides, diketones, aldehydes and hydroxylamine employing conventional or multi-component cyclocondensation reaction procedures. When the reactions were carried out in dichloromethane as solvent and DAST in slight excess (1:2), at room temperature for a reaction time of 24 hours, it was observed monofluorination reactions on 4-hydroxyalkyl-1H-pyrazoles (2) (70-75%), difluorination reactions in 4-formylethyl-1H-pyrazoles (4e) (71%), intramolecular cyclization on 4-hydroxyalkyl-4,5-dihydro-1H-pyrazoles (6) (74-80%) and dehydration reactions in 3-(alkyl/aryl)-4,5-dihydropyrazoles (8) (65-75%). Reactions of 2-hydroxy-2H-chromenones (10-14) with DAST by similar reactions conditions, were chemoselective, despite the various reactive sites present in these compounds, and exclusively by the SN2 nucleophilic substitution at the C-2-, conduted to the monofluorinated tetrahydro-2H-chromenones (15-19) (63-81 %). Finally, despite the partial structural similarity with 2-hydroxy-2H-cromenones (10-14), were performed reactions of 4,5-dihydroisoxazoles (20) in the presence of DAST, which resulted only in dehydration products (21) (73-85%) similarly to the results for 3-(alkyl/aryl)-4,5- dihydropyrazoles (8).